Tolvaptan in Patients Hospitalized With Acute Heart Failure. (September 2015) - Felker, G. Michael; Mentz, Robert J.; Adams, Kirkwood F.; Cole, Robert T.; Egnaczyk, Gregory F.; Patel, Chetan B.; Fiuzat, Mona; Gregory, Douglas; Wedge, Patricia; O'Connor, Christopher M.; Udelson, James E.; Konstam, Marvin A.
<x xml:space="preserve">Abstract</x> Congestion is a primary reason for hospitalization in patients with acute heart failure (AHF). Despite inpatient diuretics and vasodilators targeting decongestion, persistent congestion is present in many AHF patients at discharge and more severe congestion is associated with increased morbidity and mortality. Moreover, hospitalized AHF patients may have renal insufficiency, hyponatremia, or an inadequate response to traditional diuretic therapy despite dose escalation. Current alternative treatment strategies to relieve congestion, such as ultrafiltration, may also result in renal dysfunction to a greater extent than medical therapy in certain AHF populations. Truly novel approaches to volume management would be advantageous to improve dyspnea and clinical outcomes while minimizing the risks of worsening renal function and electrolyte abnormalities. One effective new strategy may be utilization of aquaretic vasopressin antagonists. A member of this class, the oral vasopressin-2 receptor antagonist tolvaptan, provides benefits related to decongestion and symptom relief in AHF patients. Tolvaptan may allow for less intensification of loop diuretic therapy and a lower incidence of worsening renal function during decongestion. In this article, we summarize evidence for decongestion benefits with tolvaptan in AHF and describe the design of the Targeting Acute Congestion With Tolvaptan in Congestive Heart Failure Study (TACTICS) and Study to Evaluate Challenging Responses to Therapy in Congestive Heart Failure (SECRET of CHF) trials.